Manoalide Shows Mutual Interaction between Cellular and Mitochondrial Reactive Species with Apoptosis in Oral Cancer Cells. (2nd March 2021) - Wang, Hui-Ru; Chen, Ping-Ho; Tang, Jen-Yang; Yen, Ching-Yu; Su, Yong-Chao; Huang, Ming-Yii; Chang, Hsueh-Wei
Abstract : We previously found that marine sponge-derived manoalide induced antiproliferation and apoptosis of oral cancer cells as well as reactive species generations probed by dichloro-dihydrofluorescein diacetate (DCFH-DA) and MitoSOX Red. However, the sources of cellular and mitochondrial redox stresses and the mutual interacting effects between these redox stresses and apoptosis remain unclear. To address this issue, we examined a panel of reactive species and used the inhibitors of cellular reactive species ( N -acetylcysteine (NAC)), mitochondrial reactive species (MitoTEMPO), and apoptosis (Z-VAD-FMK; ZVAD) to explore their interactions in manoalide-treated oral cancer Ca9-22 and CAL 27 cells. Hydroxyl (˙OH), nitrogen dioxide (NO2 ˙), nitric oxide (˙NO), carbonate radical-anion (CO3 ˙– ), peroxynitrite (ONOO – ), and superoxide (O2 ˙– ) were increased in oral cancer cells following manoalide treatments in terms of fluorescence staining and flow cytometry. Cellular reactive species (˙OH, NO2 ⋅, ˙NO, CO3 ˙–, and ONOO – ) as well as cellular and mitochondrial reactive species (O2 ˙– ) were induced in oral cancer cells following manoalide treatment for 6 h. NAC, MitoTEMPO, and ZVAD inhibit manoalide-induced apoptosis in terms of annexin V and pancaspase activity assays. Moreover, NAC inhibits mitochondrial reactive species and MitoTEMPO inhibits cellular reactive species, suggesting that cellular and mitochondrial reactive species can crosstalk to regulate each other. ZVAD shows suppressing effects on the generation of both cellular and mitochondrial reactive species. In conclusion, manoalide induces reciprocally activation between cellular and mitochondrial reactive species and apoptosis in oral cancer cells.